Prospect for accounting academics: examining the effect of undergraduate students’ career decision / Ahmad Bukola Uthman , Mubaraq Sanni and Abdulai Agbaje Salami - Uthman, Ahmad Bukola; Sanni, Mubaraq; Salami, Abdulai Agbaje (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
The future of accounting education rests on the development of accounting academics. In the social space of competing job opportunities for both graduate and professional accountants, this paper considers how the interest of prospective accounting graduates in Nigerian universities could reshape the widely reported shortage of accounting academics. Viewing through the lens of the Circumscription Theory, it examines how career choices of undergraduate accounting students affect the prospect of accounting education. The survey technique was adopted to sample students’ opinions across three universities in their career decisions, the factors that affect such decisions and their key referents. The respondents were divided based on their preference for academic jobs and the Mann-whitney U test was conducted to examine the differences in factors that affect their preferences. The study revealed that financial rewards account for students’ preference for non-academic jobs. Hence, only 10% of the respondents showed an intention to pursue a career in the academia. Other factors such as job leisure, ambitiousness and career prestige are also responsible for students’ preference for non-academic jobs. The results of the study confirmed the prediction of the Circumscription Theory. It is therefore recommended that academic jobs should be made attractive for accounting graduates by improving the financial rewards of academic staff generally. More so, attention should be further directed towards factors such as job leisure, holiday travels, prestige and easy achievement of ambitions since students get swayed from academic jobs because of those factors.